Onset risk factors for youth involvement in cyberbullying and cybervictimization: A longitudinal study - Sorrentino, Anna; Esposito, Alessia; Acunzo, Debora; Santamato, Margherita; Aquino, Antonio (Frontiers in Psychology, 2023)
Cyberbullying and cybervictimization are worldwide spread phenomena involving, due also to the Covid-19 pandemic, an increasing number of children and adolescents. Since the first decade of the 21st century, research has investigated and highlighted the key risk factors for cyberbullying and cybervictimization, and numerous anti-cyberbullying prevention and intervention programs have been developed and assessed for their efficacy. Despite this, no studies have specifically focused on the individual, relational and contextual risk factors associated with youth onset involvement in cyberbullying and cyber victimization. To this aim, 333 Italian students aged 10-16 years (M=12.16, SD= 1.35) were involved in a 1-year longitudinal study and filled in the anonymous online actuarial Tabby Improved Checklist two times with a six months intervals. Onset risk factors for cyberbullying and cybervictimization have been separately analyzed by excluding from the original sample all students involved in cyberbullying or in cybervictimization at baseline (T1). The results showed that being male, involvement in school bullying, low levels of awareness of online risk, and high levels of affective empathy were all significant onset risk factors for cyberbullying. Being male, involvement in school bullying and victimization, high levels of affective empathy, and moral disengagement were found onset risk factors for cybervictimization. Given the negative psychological and behavioral consequences of cyberbullying and cybervictimization; results will be discussed in terms of practical and policy implications for future research, stressing the need to develop, implement and evaluate the effectiveness of primary prevention programs addressing and managing onset risk factors for cyberbullying and cybervictimization.